Modifiable environmental factors predispose term infants to bronchiolitis but bronchiolitis itself predisposes to respiratory sequelae. Issue 3 (27th December 2021) - Frassanito, Antonella; Nenna, Raffaella; Arima, Serena; Petrarca, Laura; Pierangeli, Alessandra; Scagnolari, Carolina; Di Mattia, Greta; Mancino, Enrica; Matera, Luigi; Porta, Daniela; Rusconi, Franca; Midulla, Fabio
Abstract: Introduction: Viral bronchiolitis is a common lower respiratory tract infection in infants. Environmental and genetic factors can favor respiratory tract infections. Aim: The aim of this study is to analyze risk factors for bronchiolitis and to investigate the predisposing factors for developing transient wheezing and asthma through a 6‐year follow‐up after hospitalization for bronchiolitis compared with a group of healthy controls that belonged to Piccolipiù cohort,  who never had bronchiolitis. Methods: We enrolled 645 infants hospitalized with bronchiolitis. A structured questionnaire was used to obtain demographic and clinical data. At 6 years of age, 370 cases and 183 controls were investigated for the presence of asthma by the structured questionnaire, for prick test and for spirometry, and were classified to asthmatic, transient wheezing, and no wheezing/no asthma. Results: Breastfeeding was an independent protective factor (odds ratio [OR]: 0.3, 95% confidence interval [95% CI]: 0.2–0.4, p  < 0.001) and tobacco smoke was a risk factor for the development of bronchiolitis (OR: 2.1, 95% CI: 1.4–3.1, p  < 0.001). Analyzing follow‐up, bronchiolitis increased the risk of developing transient wheezing by 12.9 (95% CI: 6.3–26.1, p  < 0.001) and of developing asthma by 4.6 (95% CI: 1.9–10.7, p  < 0.001). A positive family history of atopy increased the risk of developing asthma by 3.1 (95% CI: 1.4–6.7, p  = 0.005). Asthmatic patients had a lower % FEV1, a lower % flow‐volume curve (FVC), and a lower FEV1/FVC value, and they had more frequently positive skin prick test. Conclusion: Bronchiolitis is influenced by environmental factors: tobacco smoke increases its risk and breastfeeding is a protective factor. At the end of 6 years of follow‐up, bronchiolitis is a significant risk factor to have pre‐school wheezing and asthma.